(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The two researchers used experimental methods in the first year of study at the Erbil Institute of Physical Education. The students (132) were divided into four sections, and a sample was selected for the research (2008-2009). If the two researchers will select three sections (branches) containing (16) students in each group and represent means of the research physical and skilful tests in hand-ball. The two researchers took equivalence separation of three groups in the variables, which plays an effective role in an experimental variable. Furthermore, after statistically resolving data, using tests (C) for similar samples, as well as tests (V) and (LSD), a group of conclusions were reached. Several factors contributed to the excellence of separation of the second experimental group, which was taught according to cooperative learning using the station style. The first control group was taught according to the observed (impressive) style in the skills (aiming, handing over, and taking over, racket (racquet). The two researchers recommended the significance of using the station style in accordance with cooperative learning in teaching the specific (particular) skill of handball which is better than the station style according to the self-learning and the imperative style.